ETIKA KERJA DALAM TRADISI KENABIAN VERSI KANTIAN - M. Ramin, Maghfur (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2025)
Without integrity, conflicts of interest, intimidation, privacy violations, and discrimination contribute to a disharmonious work environment and may ultimately undermine an institution's reputation. These concerns have necessitated a more rigorous library-based inquiry into work ethics within the prophetic tradition, analyzed through the lens of Immanuel Kant's ethical framework. The findings suggest that work ethics constitute a fundamental component of Islamic teachings, significantly influencing job satisfaction and professional conduct. This ethical framework encompasses key values such as diligence, teamwork, honesty, and accountability. Furthermore, essential attitudes—particularly for Muslim professionals—include a well-defined purpose in work, a principled approach to wealth, and an awareness of the temporal significance of labor. These values possess a universal character and are applicable across diverse professional settings. The implementation of ethical work principles has demonstrable positive effects on performance, reinforcing an employee’s professional integrity. Aligning occupational practices with ethical standards cultivates an authentic work ethos, characterized by honesty, discipline, creativity, responsibility, and autonomy.